Higher education as determinant of competitiveness and sustainable development of economy - Krstić, M.; Filipe, J.; Neto, J. (Sustainability, 2020)
The aim of this paper is to study the interdependence between higher education, on the one hand, and the competitiveness of the economy and sustainable development, on the other. The analysis is, primarily, based on the methodology of the Global Competitiveness Index 4.0 applied by the World Economic Forum (WEF). In order to examine the interedependence between higher education, and competitiveness of the economy and sustainable development, we used a sample from EU Member States and candidate countries. The research was conducted by using the correlation and the regression analysis. The results of the research show that there is a very strong correlation between higher education and the level of competitiveness of the economy and sustainable development. The obtained results of this research can serve as a "global benchmark" for future public policy in the field of higher education.